THE FEASIBILITY OF LOW COST AIRLINES IN KAOHSIUNG, SOUTHERN CITY OF TAIWAN - Cheng, Wan Tina; Chen, Chen (PEOPLE: International Journal of Social Sciences, 2016)
The budget airlines have caused tremendous impact in air business and travel population. Even though the budget airlines in Europe and USA are already quite popular, the budget airlines are still new in Taiwan. Pearson (2014) suggested that LCCs now are growing particularly within Asia-Pacific. Since then, there have been many studies about LCCs strategies or models, or the competitions between full-service airlines, but few have focused on the relationship between geographical locations and budget airline routes. That is, whether the LCCs’ flying routines, almost on local city or sub-airports, will help the prosperous tourism business of the local city, Kaohsiung City, a southern city of Taiwan.